2017
DOI: 10.3151/jact.15.426
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tortuosity on Chloride Ion Diffusion in Slag-Blended Cementitious Materials

Abstract: The purpose of this study is to determine the tortuosity of cementitious materials containing blast furnace slag (BFS). Furthermore, the influence of tortuosity on multi-species transport into these materials is studied. The porosity and diffusivity of calcium silicate hydrate (C-S-H) were predicted using a three-dimensional spatial distribution model, which were then fitted to Archie's law to determine tortuosity. The tortuosity increased with the slag replacement ratio, suggesting that the diffusion path for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Backscattered electron image (BEI), energy dispersive X-ray spectrometry (EDX), electron probe microanalyzer (EPMA), micro-elastic modulus, and thermoporometry measurements were conducted on the cured and exposed specimens. The details of the composition of raw materials and their physical properties as well as the experimental techniques are described in our previous paper [6].…”
Section: Materials Specimen Preparation and Experimental Methodsmentioning
confidence: 99%
“…Backscattered electron image (BEI), energy dispersive X-ray spectrometry (EDX), electron probe microanalyzer (EPMA), micro-elastic modulus, and thermoporometry measurements were conducted on the cured and exposed specimens. The details of the composition of raw materials and their physical properties as well as the experimental techniques are described in our previous paper [6].…”
Section: Materials Specimen Preparation and Experimental Methodsmentioning
confidence: 99%
“…It is an undeniable fact that cementitious materials are inherently porous in nature, possessing pores of various scales. Diffusion, the primary mode of mass transport, has been comprehended by devising effective diffusion coefficients which properly reflect the characteristics of the pore network structure (tortuosity, connectivity, constrictivity, formation factor [10,11,12,13,14,15]) and by utilizing them to solve the diffusion equation. It is obvious that the probabilistic displacement distribution is Gaussian when the conventional diffusion equation is resolved [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Yamaguchi et al refined the empirical relationship by assessing the accessible capillary pores, and demonstrated that the modified model is efficacious in describing the effective diffusion coefficient of tritiated water [69]. Furthermore, the empirical effective diffusive coefficient has been adapted to include semi-empirical parameters that characterize the morphology of the pore network (tortuosity, connectivity, constrictivity, formation factor) [10,11,12,13,14,15]. There has been extensive research aimed at relating these parameters to the actual pore topology obtained from imaging techniques, rather than simply adjusting bulk diffusion coefficients to effective diffusion coefficients [70,71,10,66,72,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…In the current RTMs [10,[12][13][14], the ion mass transport is performed only through free water space, whereas the ions in the EDL are considered stagnated ions, which means that part of cations is neglected in the ion mass transport calculation. In addition, the ion mass transport in porous materials strongly depends on temperature [23], composition and ionic strength of pore solution [24,25], and pore structure [26,27]. Pore solution composition, phase assemblage, and pore structure will continuously vary in a cement-based material due to exposure to long-term environmental actions.…”
Section: Introductionmentioning
confidence: 99%